STUDI PENCAMPURAN SERAT ECENG GONDOK SISTEM HOT ROLLED SHEET BC SPESIFIKASI SEKSI-6 : 2010 BINA MARGA - Heru Prasetyo; Samsul Arif (Litbang Pemas - Universitas Islam Lamongan, 2018)
HRS-BC (Hot Roller Sheet) is a type of flexible pavement construction because it uses asphalt as a binder between the aggregates. This study uses water hyacinth as a substitute for cellulose fiber in the mixture of HRS-BC. The purpose of this study is to determine the effect of water hyacinth cellulose fiber in HRS mixture to the Marshall characteristics. This research uses trial and error method, resulting 7.19 % asphalt content to the total aggregate weight with the variation of cellulose fibers are 3%, 4%, 5%, 6% and 7%. Marshall Test is performed to determine the effect of adding the cellulose fiber in the mixture to the components of Marshall Properties, for example Marshall Stability, % of Void Filed With Asphalt (VFWA), % of Void in The Mix (VIM), Plastic Fatigue (Flow), and Marshall Quotient (MQ).The result of this study is Marshall evaluation where the greatest score is obtained for stability of 1601 kg, flow of 4.60 mm, Quotient Marshall of 375.44 kg/mm, VMA of 20.45%, VFWA of 86.79 %, and VIM score of 4.19 %. It shows that the best cellulose fiber content is 3 % of asphalt level of 7,19 % and has been in accordance with Bina Marga 2010 Division 6 specification and can be used in asphalt mixture of HRS-BC.